Washington state satellite HIV clinic program: a model for delivering highly effective decentralized care in under-resourced communities*. Issue 9 (2nd September 2018) - Wood, Brian R.; Bell, Christopher; Carr, Jason; Aleshire, Richard; Behrens, Christopher B.; Dunaway, Shelia B.; Shah, Javeed A.; Barnabas, Ruanne V.; Green, Margaret L.; Ramers, Christian B.; Fina, Pegi L.; Kim, H. Nina; et al.
ABSTRACT: To improve access to high-quality HIV care in underserved regions of Western Washington (WA) State, we collaborated with the WA State Department of Health (DOH) and community partners to launch four satellite HIV clinics. Here, we describe this innovative clinical care model, present an estimate of costs, and evaluate patient care outcomes, including virologic suppression rates. To accomplish this, we assessed virologic suppression rates 12 months before and 12 months after the satellite clinics opened, comparing people living with HIV (PLWH) who enrolled in the satellite clinics versus all PLWH in the same regions who did not. We also determined virologic suppression rates in 2015 comparing satellite clinic versus non-satellite clinic patients and compared care quality indicators between the satellite clinics and the parent academic clinic. Results demonstrate that the change in virologic suppression rate 12 months before to 12 months after the satellite clinics opened was higher for patients who enrolled in the satellite clinics compared to all those in the same region who did not (18% versus 6%, p < 0.001). Virologic suppression in 2015 was significantly higher for satellite clinic than non-satellite clinic patients at three of four sites. Care quality indicators were met at a high level at the satellite clinics, comparable to the parent academic clinic. Overall, through community partnerships and WA DOH support, the satellite clinic program increased access to best practice HIV care and improved virologic suppression rates in difficult-to-reach areas. This model could be expanded to other regions with inadequate access to HIV practitioners, though financial support is necessary.